Discovering Copper Uptake in Aquatic Organisms by Analytical Chemistry and Study of Bioaccumulation, Toxicity, and Ecological Implications - Shaziya Mohammed Irfan Momin (The Bioscan, 2025)
Copper is an essential trace metal, but in elevated concentrations, it can be toxic to aquatic organisms. Understanding its uptake, bioaccumulation, and ecological effects is crucial for assessing environmental health. The concentrations of heavy metal Copper (accumulation) in Tilapia fish organs (muscle, gills, kidney and liver) were investigated. Fish organs from Varal Devi Lake showed greater concentrations of studied metal than those from the standard value.The amount of copper absorbed by kidney is much higher than the other organs. The order of organs infected by Copper metals are as follows. Kidney>Liver>Gills = Abdominal Muscles Kidney and Liver of Tilapia contained the highest concentration of the detected heavy metal, while muscles and gills exhibit the same amount and least amount of absorption. This study were carried out during the Ganesh Chaturti festival period as this lake is used for Idol immersion activity. Tilapia caught from this Lake may pose health hazards for consumers. KEYWORDS Copper, Fish Organs,Varal Devi Lake, Spectrophotometer.